Pengaruh Motivasi Organisasi Dan Keaktifan Berorganisasi Terhadap Indeks Prestasi Mahasiswa Unit Kegiatan Mahasiswa Universitas Muhammadiyah Surakarta - Alashfahani, Dyan Sani Febrian, Dra. Sri Hartini, S.H, M.Pd (2016)
GPA is a result of study. GPA is influence by some factors include organization, is organization motivation and activate of student in organization. The purpose of this research is looking for : 1) is there any influence of motivation of organization for student's GPA; 2) is there any influence oc activation of organization for student's GPA; 3) is there the influence of student work and motivation on organization in student's GPA Units of Student Activity In University Of Muhammadiyah Surakarta. Type of this research is descriptive quantity to describe object of the research and doing hypothesis. Population of this research is all of active member units of student activity from 50 students School of Teacher Training and Education. Samples of this research is a 30 students years 2012 - 2014 from School of Teacher Training and Education with proportioned stratified random sampling. The technique of data collection using questionnaire, observation, documentation methode. The first step is arrange the questionnaire that tasted and validity and reliability test for knowing that can be validly and questionnaire reliability. Data analysis technique used by F test and T test. The result of analysis of showing of influence that positive and signified between 1) motivation of organization for student's GPA. The result t count > t table (2,360 > 2,052) with significance 5%. 2) activation of organization for student's GPA. The results is t count > t table (2,177 > 2,052). 3) student work and motivation on organization in student's GPA. The result of F count > F table (3,625 > 3,35). So, it can conclude that there is a significance influence between motivation organization activity of students on organization to student's GPA.